Validity, reliability, and the factorial structure of bangla version depression, anxiety, and stress scale (DASS-21) among Bangladeshi healthcare professionals - Shakil Ahmed; Humayun Kabir; Fabeha Tazmeem; Tachlima Chowdhury Sunna; Tajrin Tahrin Tonmon; Sarker Md. Nasrullah; Prodip Chandra Roy; Saifur Rahman Chowdhury (Discover Psychology, 2024)
Abstract Objective The objective of this study was to assess the validity, reliability, and factorial structure of the Bengali-translated Depression, Anxiety, and Stress Scale—21 (DASS-21) among Bangladeshi health professionals. Methods This study incorporated the cross-sectional study design, conducted among 312 health professionals from 28 health facilities in 18 districts across Bangladesh. The internal consistency and intraclass correlation coefficient of the DASS-21 was assessed. The confirmatory factor analyses was done to assess the fitness of different structural models of DASS-21. The concurrent validity was estimated by using the PHQ-9 and GAD-7 scales. Results In total, 258 healthcare professionals (82.7%) out of 312 completed the whole survey questionnaire and were included in the study. The internal consistency of the DASS-21 exhibited satisfactory internal consistency (α = 0.93) and ICC = 0.92). The conventional three-factor model appeared to best fit the Bengali-translated DASS-21 scale. The discriminant validity has been affirmed by strong evidence. The convergent validity of Bengali DASS-21 was confirmed by the PHQ-9 and GAD-7 scales. Conclusions This study found good validity, reliability, and suitability of the DASS-21 used among the Bangladeshi healthcare professionals. We warrant future research to explore the validity of this tool in other cohorts in Bangladesh.